2019
DOI: 10.1111/eea.12863
|View full text |Cite
|
Sign up to set email alerts
|

Soil conservation practices for insect pest management in highly disturbed agroecosystems – a review

Abstract: Decline in soil health is a serious worldwide problem that decreases complexity and stability of agricultural ecosystems, commonly making them more prone to outbreaks of herbivorous insect pests. Potato (Solanum tuberosum L., Solanaceae) and onion (Allium cepa L., Amaryllidaceae) production is currently characterized by high soil disturbance and heavy reliance on synthetic inputs, including insecticides. Evidence suggests that adopting soil conservation techniques often (but not always) increases mortality and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 228 publications
(327 reference statements)
1
31
0
1
Order By: Relevance
“…The 10% BM treatment increased both yield and production accompanied by increased disease severity. Overuse of mineral/synthetic fertilizers have been reported in literature as increasing pest and disease incidence or severity [17,18,32,33]. Our study draws attention to overuse of organic fertilization source that may also induce a higher severity of plant disease.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The 10% BM treatment increased both yield and production accompanied by increased disease severity. Overuse of mineral/synthetic fertilizers have been reported in literature as increasing pest and disease incidence or severity [17,18,32,33]. Our study draws attention to overuse of organic fertilization source that may also induce a higher severity of plant disease.…”
Section: Discussionmentioning
confidence: 75%
“…However, on potato (Solanum tuberosum L.), experiments showed that no application of nitrogen led to higher attack of A. solani [16]. Nitrogen source also affects plant metabolism, changing susceptibility to a pathogen [17][18][19]. Ammonium nitrogen triggered a decrease in calcium uptake and was responsible for an increase in sweet basil (Ocimum basilicum L.) plant susceptibility to grey mold (Botrytis cinerea) [19].…”
Section: Introductionmentioning
confidence: 99%
“…Grondbewerkingen kunnen nadelig zijn voor zowel de in de bodem levende plaag als de predator en de uitkomst is niet altijd eenduidig. Over het algemeen draagt gereduceerde grondbewerking bij aan het beheersen van plagen door een toename van de populatie natuurlijke vijanden, maar de resultaten zijn afhankelijk van het gewas en de plaag (Alyokhin et al, 2020). Edwards (1975) zag een toename van slakken en ritnaalden in graan en koolzaad waar niet werd geploegd ten opzichte van de controle waar wel werd geploegd.…”
Section: Grondbewerkingunclassified
“…Chavan et al (2010) reported 28.13 per cent avoidable yield loss due to major sucking pests in cotton. Among these whitefly and jassid is the deadliest pest and reduces the crop yield to a great extent (Alyokhin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%